2011
DOI: 10.1002/smll.201100746
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of Near‐Infrared Fluorescent Gold Clusters for Cellular Fluorescence Lifetime Imaging

Abstract: A facile strategy to synthesize water‐soluble fluorescent gold nanoclusters (Au NCs) stabilized with the bidentate ligand dihydrolipoic acid (DHLA) is reported. The DHLA‐capped Au NCs are characterized by UV–vis absorption spectroscopy, fluorescence spectroscopy, transmission electron microscopy, and X‐ray photoelectron spectroscopy. The Au NCs possess many attractive features including ultrasmall size, bright near‐infrared luminescence, high colloidal stability, and good biocompatibility, making them promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
295
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 348 publications
(312 citation statements)
references
References 71 publications
15
295
0
2
Order By: Relevance
“…[13][14][15] In optical imaging, one of the great advantages of Au NCs compared to plasmonic Au nanoparticles (Au NPs) is related to the ability to visualize them by fluorescence in the red-near-infrared (NIR) region (650-800 nm), a spectral window suitable for in vivo studies due to the reduced tissue scattering and low blood absorption. 16,17 In addition, the high electronic number of gold (Z = 79) allows the detection of gold particles by computed X-ray tomography (CT) 5 and by photoacoustic imaging (PAI). 18,19 With the development of new contrast agents such as gold nanorods and nanocages, PAI combines the most compelling features of optical imaging and ultrasound imaging, providing both high optical contrast and high resolution ultrasound including in vivo in deep tissues.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%
“…[13][14][15] In optical imaging, one of the great advantages of Au NCs compared to plasmonic Au nanoparticles (Au NPs) is related to the ability to visualize them by fluorescence in the red-near-infrared (NIR) region (650-800 nm), a spectral window suitable for in vivo studies due to the reduced tissue scattering and low blood absorption. 16,17 In addition, the high electronic number of gold (Z = 79) allows the detection of gold particles by computed X-ray tomography (CT) 5 and by photoacoustic imaging (PAI). 18,19 With the development of new contrast agents such as gold nanorods and nanocages, PAI combines the most compelling features of optical imaging and ultrasound imaging, providing both high optical contrast and high resolution ultrasound including in vivo in deep tissues.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%
“…In recent years, fluorescent AuNCs have been used for cellular FLIM owing to their long lifetimes. For example, Shang et al reported biocompatible DHLA-stabilized AuNCs as labels in FLIM with long fluorescence lifetime ([100 ns) [147]. The results indicated that DHLA-AuNCs have great potential as fluorophores in biomedical applications, especially in combination with FLIM.…”
Section: Biological Imagingmentioning
confidence: 99%
“…Although this strategy proved to be efficient for synthesizing AuNCs with different ligands, it involves a multi-step process that makes their synthesis rather complicated and tedious. By contrast, a one-step strategy, in which fluorescent AuNCs are produced directly by reducing gold salt with a suitable reductant such as sodium borohydride (Link et al 2002;Schaeffer et al 2008;Shang et al 2011a), tetrakis(hydroxymethyl)phosphonium chloride (Shang et al 2011b), or even proteins (Xie et al 2009;Xavier et al 2010;Wen et al 2011;Yan et al 2012), is more favorable and has lately been widely adopted.…”
Section: Optical Properties and Synthesis Of Gold Nanoclustersmentioning
confidence: 99%
“…Consequently, fluorescence lifetime imaging may provide contrast due to spatial variations of the lifetime and, thus, may yield valuable additional information (Borst and Visser 2010). We have recently introduced a facile strategy of synthesizing near-infrared-emitting lipoic acidcoated AuNCs (Shang et al 2011a). Besides ultrasmall size, good colloidal stability, and biocompatibility, these AuNCs possess a long fluorescence lifetime (>100 ns), much longer than that of cellular autofluorescence and the fluorescence of organic dyes, so that, by using timegated detection, their emission can be detected absolutely background-free.…”
Section: Fluorescence Imaging Of Gold Nanoclusters In Vitromentioning
confidence: 99%